Duck on a disco ball - Mack, Jeff (Mack, Jeff. Duck in the fridge book., 2018)
"Every night it's the same old story. A boy wants to stay up late, and his parents won't let him. But sometimes in the morning, he notices things look a little off--like when he sees a disco ball in the kitchen ... with his toy duck on it. So one night he decides to stay up. And that's when the fun really begins."--